Characterization and strengthening mechanism of CNT/TiB2 particulates added AZ91D composites. (1st March 2023) - Velmurugan, V; Mohan, B
Abstract: In the current work, magnesium (AZ91D) matrix composites reinforced with different weight fractions (5, 10, and 15%) of titanium diboride (TiB2 ) and 1.5 wt% carbon nanotubes (CNTs) are fabricated using stir casting. The improvements in mechanical, wear and corrosion resistance properties are evaluated as per ASTM guidelines. The synergistic strengthening effect of TiB2 and CNT is also studied. It was discovered that the AZ91D/(1.5CNT-10TiB2 ) composite outperformed other magnesium matrix composites in terms of strength and ductility. Experimental characterization and quantity analysis revealed that the load transfer process of CNT, thermal mismatch, and grain refinement are the primary factors leading to the composite's increased tensile strength. Porosity tends to increase due to variance in the thermal expansion coefficient of particles and matrix material; Orowan strengthening mechanism plays a prominent role in enhancing tensile strength. Because of the influence of synergistic strengthening, microparticles TiB2 increased the proportion of load transmission mechanisms, and thermal mismatch facilitated the homogenous distribution of CNTs. Wear resistance and corrosion resistance increase with the inclusion of CNTs and TiB2 content. An abrasive-type wear mechanism is seen in the SEM image, and the wear craters are also seen in all the SEM images. Adding TiB2 significantly improves the cast composites' resistance to corrosion because of grain refinement. Higher addition of TiB2 influences higher pitting corrosion due to poor grain refinement.